If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6 = 10x Reorder the terms: -6 + 4x = 10x Solving -6 + 4x = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -6 + 4x + -10x = 10x + -10x Combine like terms: 4x + -10x = -6x -6 + -6x = 10x + -10x Combine like terms: 10x + -10x = 0 -6 + -6x = 0 Add '6' to each side of the equation. -6 + 6 + -6x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -6x = 0 + 6 -6x = 0 + 6 Combine like terms: 0 + 6 = 6 -6x = 6 Divide each side by '-6'. x = -1 Simplifying x = -1
| 21+29x=42+22x | | 81k^2-49=0 | | -[4z-(12z+6)]=6+(7z+7) | | 8-2a=-12 | | 11=7(x-3)+21 | | 0.4c+4+-5c=-9 | | 11= | | 9x-13-8x=29 | | 36+4r=-4(r+7) | | -10x=260 | | 7(x+7)=2x+57 | | 138-4=2l+4-4 | | 6z+z=6z+9 | | 3x+6=4w | | .2x=7-.6x | | 1-5x=-4-4x | | -11x+9-4x=2 | | y/4=15/6 | | 7s-5-7s+9= | | 10.9x+15.56=-9.1x+13.86 | | m+3-2=7 | | 10.9x+15.56=9.1x+13.86 | | 4x-22=3x+17 | | A=x+xtd | | 7s-5-7s+5= | | 15=5x+x+7 | | 1-3/4= | | 2xy=6 | | 5x-2x+8=29 | | c=10*1/2 | | 2x=10*1/2 | | y=3.25x+40 |